Sarcoptes scabiei infestation in llamas (Lama glama) of the Argentine Puna: Clinical study, and morphological and molecular mite identification - Sosa, Fabiana Evangelina (2025)
Sarcoptic mange has been described in domestic South American camelids (SACs), exported to non-Andean countries, and in wild SAC in their natural habitat. Reports on the incidence of this infestation in llamas or alpacas raised in their original location, on the other hand, are missing. The present study aimed to detect and characterize cases of sarcoptic mange in herds of llamas (Lama glama) raised in the high plateau region (Puna) of the province of Jujuy, Argentina. Mange-compatible lesions were found in 2 out of 45 examined llama herds, in which 7 and one affected animals were detected. Six llamas had an alopecic presentation, represented by hairless foci, accompanied by small dry crusts and a slightly greyish tone in the skin, while the other 2 showed a parakeratotic presentation, characterized by large crusts with serosanguineous drainage, in different parts of the body. Histopathology of skin biopsies revealed scarce mixed inflammatory infiltrate in the dermis and few acari in the epidermis, or abundant infiltrate and numerous acari, accompanying these two presentations, respectively. Microscopic examination of skin scrapings, as well as sequencing of a cytochrome oxidase subunit I gene fragment confirmed in all cases that the etiological agent was Sarcoptes scabiei. Interviews with the producers allowed the conclusion that the alopecic presentation corresponded to animals that had received some type of informal acaricide treatment. The parakeratotic form, on the other hand, corresponded to untreated animals, strongly suggesting that this is the typical manifestation of sarcoptic mange in llamas. To the best of our knowledge, this study is the first clinical, histopathological, parasitological, and molecular description of sarcoptic mange in llamas raised in the Andean region. This study also highlights the need for a complete anamnesis to reach an accurate diagnosis, and for validated protocols for the treatment of this disease in SACs.